KESALAHAN SINTAKSIS TULISAN MAHASISWA ASING PROGRAM STUDI PENDIDIKAN BAHASA INDONESIA UNIVERSITAS BINA DARMA - Muchti, Andina (Direktorat Riset dan Pengabdian pada Masyarakat (DRPM) Universitas Bina Darma, 2018)
Study has objectives, (1) describe the mistakes in the language in the field of syntax in the essay writing of foreign students in the regular class, and (2) describe the analysis of the mistakes in the language in the field of syntax in the essay writing of foreign students in the regular class in Bina Darma University. This research is a descriptive qualitative research. Sources of data in this study iswriting of foreign students in the regular class in UBD. The data is a form of language errors in the essay writting. Analyzed using a unified method and agih. Results can be divided into nine aspects, there are (1) sentence structure not standard, (2) sentence is ambiguous, (3) sentence is unclear, (4) diction is not appropriate in forming sentences, (5) contamination sentence, (6) coherence, (7) word redundant, (8) the word uptake used in a sentence, and (9) logic sentence.